Utilization Ecdysterone Hormone of Krokot (Portulaca oleracea) Extract on Molting Activity in Mud Crabs (Scylla serrate) - Ihsan, Gusti Abdillah; Widodo, Maheno Sri; Faqih, Abd. Raheem; Paricahya, Akhsan Fikrillah (Postgraduate, University of Mataram, 2024)
The Scylla serrate mangrove crab is one of the leading fisheries commodities in terms of exports, only behind shrimp, tuna and shellfish. Crabs have a fairly high price in foreign markets and most of the mud crabs obtained from wild catches are soft shell crabs. In terms of price, cultivating soft shell crabs is quite profitable, but most cultivators have several problems such as long maintenance periods and inconsistent molting times so that they do not experience business continuity. Applying herbal extracts via injection is an effective method because all the substances that trigger molting directly enter the body. Physiological engineering is needed to speed up the molting phase and get the same molting time. This research aims to identify the ecdysterone content in purslane leaves and determine the optimum dose of purslane leaf extract which can encourage skin molting in mud crabs. This research used a Randomized Block Design (RBD). The in silicons test results show that the compound that has the smallest binding affinity is ecdysone, namely -6.80 kcal/mol. Based on analysis of variance, the best molting percentage occurred in treatment B at 55.50%. The fastest molting period occurred in treatment C, namely on days 4 to 29 after injection. Treatments B and C had the highest survival rate, namely 100%, while in terms of increasing body weight and carapace width, the effect of all treatments was not significantly different. The water quality results for all groups were still within the optimum value, temperature 26.40 – 33.80ºC; pH 6.83 – 7.20; salinity 20.70 – 26.70 ppt and dissolved oxygen 4 – 4.52 ppm